The Effect of Carthamus tinctorius in Combination with Dexamethasone on Coagulation Markers in Mice Induced by SARS-CoV2 Spike Protein - Yantirta Kurniawan; Melva Louisa*; Beti Ernawati Dewi; Lismayana Hansur; Jamal Zaini; Ari Estuningtyas (Iranian Society of Pharmacognosy, 2023)
Background and objectives: COVID-19 is a respiratory condition frequently followed by an inflammatory reaction in addition to respiratory symptoms, which disrupts the blood coagulation process. One drug candidate known to have dual anti-inflammatory and anticoagulating effects is hydroxysafflor yellow A, an active compound found in the flowers of Carthamus tinctorius. Therefore, this study analysed the effect of C. tinctorius ethanol extract in combination with dexamethasone on coagulation biomarkers in mice induced with the SARS-CoV2 spike protein. Method: Flowers of Carthamus tinctorius were extracted with 98% ethanol. The concentrated extract was used in the study. Twenty-five Balb/c mice, comprising five healthy controls and twenty mice were induced with SARS-CoV2. The SARS-CoV2-induced mice were then randomized to receive seven days of treatment, which consisted of vehicle or dexamethasone 2.5 mg/kg BW, dexamethasone 2.5 mg/kg BW + C. tinctorius extract 400 mg/kg BW, or dexamethasone 2.5 mg/kg BW + C. tinctorius extract 800 mg/kg BW. Subsequently, the lungs and blood of the mice were analysed. Results: SARS-CoV2-induced mice increased all the coagulation markers studied. Treatment with dexamethasone alone or in combination with C. tinctorius extract 400 mg/kg BW did not cause reductions in D-dimer, plasminogen activator inhibitor-1, lactate dehydrogenase, platelet-to-leucocyte ratio, or neutrophil-to-leucocyte ratio. However, dexamethasone co-treatment with C. tinctorius extract at 800 mg/kg BW resulted in the normalization of D-dimer, PAI-1, and NLR in SARS-CoV2-induced mice. Conclusion: The administration of high dose of C. tinctorius flower extracts (800 mg/kg BW) in combination with dexamethasone showed the benefit of minimizing the coagulation disorder in SARS-CoV2.